Chemical Composition and Biological Activities of Essential Oils from Two Wild Algerian Medicinal Plants: Mentha pulegium L. and Lavandula stoechas L. Issue 3 (4th May 2019) - Baali, Faiza; Boumerfeg, Sabah; Napoli, Edoardo; Boudjelal, Amel; Righi, Nadjat; Deghima, Amirouche; Baghiani, Abderrahmane; Ruberto, Giuseppe
Abstract: The aim of the present study was to determine the chemical composition, antioxidant and antimicrobial activities of Algerian Mentha pulegium L. and Lavandula stoechas L. essential oils (EOs). The essential oils of M. pulegium and L. stoechas were obtained by hydrodistillation and their yields was 3.96 ± 0.12 and 1.46 ± 0.06 % (v/w), respectively. GC-MS analyses allowed the identification of 27 components representing 98.06 % of the total oil for M. pulegium, and 68 components representing 93.51 % of the total for L. steochas. The main components of M. pulegium EO were pulegone (81.04 %), piperitenone (13.60 %) and trans-p -mentha-8-en-3-one (1.35 %). Fenchone (50.29 %), camphor (14.02 %) and bornyl acetate (5.60 %) were the main components of L. stoechas EO. The antioxidant activity of EOs was estimated by total antioxidant capacity, DPPH and ABTS radical scavenging assays, ferric-reducing power test and β-carotene bleaching assay. Both EOs exhibited a moderate antioxidant activity compared to BHT, vitamin C and trolox. Antibacterial studies showed good activity against four Gram positive and Gram negative bacteria: Staphylococcus aureus, Bacillus subtilis, Pseudomonas aeruginosa, Escherichia coli, as well as good inhibitory properties (MIC), suggesting that Algerian M. pulegium and L. steochas EOs can be used in food and pharmaceutical industries as antimicrobial and preservative agents.